Assessment of the Quality and Reliability of Information on Nutrition After Bariatric Surgery on YouTube - BATAR, NAZLI; Yıldız, Nida; Güçlü, Duygu; SEVDİN, SEZEN; KERMEN, SEDA (Springer, 2020)
Background YouTube (TM) is a platform that many people, including patients, use to access health information. Recent studies have revealed that videos on YouTube (TM) are misleading or that medical videos may not contain appropriate information. This study aimed to assess the quality and reliability of videos on nutrition after bariatric surgery. Materials and Methods The keywords "after bariatric surgery diet" and "weight loss surgery postop diet" were used, and the first 100 videos for each keyword on YouTube (TM) were analyzed by considering the source, duration, content, and the number of likes of the video. The popularity of the video was calculated using the video power index (VPI) and view rate. The educational quality of the videos was evaluated using the DISCERN score, the Journal of the American Medical Association (JAMA) score, the Global Quality Score (GQS), the usefulness score, and a novel postoperation nutrition score (PONS). Results One hundred fourteen patients were included in the study. The mean duration and number of views were 12.51 min and 87,558.46, respectively. The DISCERN score, JAMA score, GQS, and usefulness score of the physicians or dietician-based videos were significantly higher than those of the patient-based videos (p < 0.001). Positive correlations were found between the VPI and view ratio, as well as between the duration and number of likes. Additionally, the DISCERN score was significant correlated with the duration and number of likes. Significantly positive correlations were found between the usefulness score and duration, usefulness score and number of likes, and PONS and duration (p < 0.01). Conclusions Informational videos on nutrition after bariatric surgery on YouTube (TM) are of low quality. Although the videos uploaded by physicians and dieticians have higher quality, only a few are available. Additionally, patients prefer to watch low-quality videos.
Keywords: Internet; YouTube; After Bariatric Surgery; Patient Education; Information; Quality Video